Using Mobile Robots to Establish Mobile Wireless Mesh Networks and Increase Network Throughput. (29th August 2012) - Nguyen, Cory Q.; Min, Byung-Cheol; Matson, Eric T.; Smith, Anthony H.; Dietz, J. Eric; Kim, Donghan
Abstract : We discuss the proof of concept that gives mobile robotic units the ability to provide a mobile wireless mesh network providing wireless service to end-clients and also demonstrate the ability to increase the throughput of this mobile wireless mesh system by autonomously reducing the hop count required for network traffic to transit through. In doing so, this proof-of-concept contributes to future development of a robust system which can be deployed and utilized in different situations and industry.